2012
DOI: 10.1007/s13311-012-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of DSM-IV Attention-Deficit/Hyperactivity Disorder: A Meta-Analytic Review

Abstract: This article describes a comprehensive metaanalysis that was conducted to estimate the prevalence of attention-deficit/hyperactivity disorder (ADHD), as defined by the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV). A systematic literature review identified 86 studies of children and adolescents (N0 163,688 individuals) and 11 studies of adults (N014,112 individuals) that met inclusion criteria for the meta-analysis, more than half of which were published after the only previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

102
1,156
30
60

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,792 publications
(1,348 citation statements)
references
References 34 publications
102
1,156
30
60
Order By: Relevance
“…Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition behaviourally defined by patterns of persistent age inappropriate inattention, hyperactivity and impulsivity [1], affecting 3-7% of children and adults worldwide [2][3][4][5]. ADHD is also characterized by cognitive difficulties [6], and impacts significantly on management of daily routines [7], school [8], work [9] and social relationships [10].…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition behaviourally defined by patterns of persistent age inappropriate inattention, hyperactivity and impulsivity [1], affecting 3-7% of children and adults worldwide [2][3][4][5]. ADHD is also characterized by cognitive difficulties [6], and impacts significantly on management of daily routines [7], school [8], work [9] and social relationships [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Research has reported ADHD prevalence estimates of approximately 5.9-7.1% in children and adolescents with a male to female ratio of approximately 3:1 in population samples and up to 10:1 in clinical samples. 1 While research has also reported various etiological factors contributing to ADHD, there is general consensus that ADHD may be classified as a neurodevelopmental disorder. In fact, the recently released DSM-5 has included it as part of this class of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…11 Conversely, a recent comprehensive meta-analyses did not detect significant differences in several assessed areas comparing subjects with different ADHD types (main comparisons between predominantly inattentive and combined types), arguing that these phenotype differences might not be so relevant. 26 Based on these findings and on the low developmental stability of ADHD types, the ADHD working group for the DSM-5 recently proposed the downgrade of the types to current presentation.…”
Section: Adhd As a Heterogeneous Disordermentioning
confidence: 99%